(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Morphometric and meristic analyses are crucial tools for distinguishing fish populations and assessing ecological adaptations within aquatic environments. This study investigated the morphometric and meristic characteristics of Oreochromis niloticus and Hepsetus odoe inhabiting the Owalla Reservoir, Osun State, Nigeria, to determine their population structure, growth patterns, and environmental responses. Ninety-eight specimens (53 O. niloticus and 45 H. odoe) were collected between July and October 2024 using gill and cast nets. Standard morphometric measurements and meristic counts were obtained and analyzed using SPSS version 22.0. Length–weight relationships (LWR) were established through regression models, while the physicochemical properties of the reservoir water were assessed to evaluate environmental suitability. Results revealed positive allometric growth in both species (b > 3), indicating improved weight gain relative to body length, with O. niloticus showing a stronger correlation (r² = 0.96) than H. odoe (r² = 0.91). The water’s physicochemical parameters, including dissolved oxygen (5.10–7.32 mg/L), temperature (24–27.6 °C), and pH (6.57–7.10), were within optimal limits for tropical fish sustainability. Statistical visualizations showed distinct linear growth trends between total length and body weight across species and age groups. The findings underscore the ecological adaptability of both species and their potential for aquaculture development.